Hot deformation behavior and microstructure evolution of NiAl-9HfO2 composite. (December 2021) - Liu, Dekai; Lu, Zhen; Yu, Jianxin; Shi, Chengcheng; Xiao, Han; Liu, Wei; Jiang, Shaosong
Abstract: The hot deformation behavior and microstructure evolution of the new NiAl-9%HfO2 composite synthesized by hot pressing sintering were researched by hot compression tests at temperatures of 1250–1400 °C and strain rates of 10 −3 -10 −1 s −1 under a true strain of 0.693. The Arrhenius constitutive model was established on account of the stress-strain curves corrected by friction and adiabatic. The processing maps were also developed and the features of microstructure inferred by the processing map were corresponded to the microstructure observation. The optimum hot deformation processing window was 1300–1350 °C/0.03–0.01 s −1 . In addition, the microstructure evolution and the softening mechanism during hot deformation were discussed in detail. Based on the room-temperature compression test, the samples deformed at 1350 °C with a strain rate of 0.03 s −1 exhibited the highest performance with the yield strength and ultimate compression deformation increasing by 22.6% and 52.2% compared with the original samples, respectively. This work provided more theoretical guidance for the hot processing of NiAl-based composites and further promoted their application. Highlights: The hot deformation behavior of a new NiAl-based composite was investigated. The Arrhenius constitutive model and processing maps were established. The microstructure evolution during hot deformation was analysed in detail. DRV and DRX under different hot deformation conditions were analysed in detail. The mechanical properties of the deformed samples were significantly improved.